2022
DOI: 10.3390/app12010434
|View full text |Cite
|
Sign up to set email alerts
|

A New System of Sustainable Silico-Aluminous and Silicate Materials for Cultivation Purpose within Sustainable Buildings: Chemical-Physical, Antibacterial and Cytotoxicity Properties

Abstract: In this study, we compared the chemical-physical, antibacterial, and cytotoxicity properties of silico-aluminous and silicate materials for outdoor (green roof, planted walls) and indoor (urban farms, indoor microgreen gardens) cultivation purpose in a context of sustainable construction. Glasses and lightweight aggregates were tailored starting from waste, by-product, and post-consumer and bioproducts (packaging glass cullet, cattle bone flour ash, vegetable biomass ash, spent coffee ground, degreased from bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…Spent coffee grounds, for example, have a neutral pH, therefore, it has been added in previous studies to neutralize the pH of PIMs that used other alkaline poring agents, such as biochar [28]. Fertilizer glass (FG), on the other hand, does not appear to affect the pH of PIMs, even though it has an alkaline pH [6]. The results obtained showed that the use of pumice scraps in the matrix instead of clay had a positive effect on the porosity of the granules, with values around 50% for Appl.…”
Section: Characterization Of Pimsmentioning
confidence: 99%
See 2 more Smart Citations
“…Spent coffee grounds, for example, have a neutral pH, therefore, it has been added in previous studies to neutralize the pH of PIMs that used other alkaline poring agents, such as biochar [28]. Fertilizer glass (FG), on the other hand, does not appear to affect the pH of PIMs, even though it has an alkaline pH [6]. The results obtained showed that the use of pumice scraps in the matrix instead of clay had a positive effect on the porosity of the granules, with values around 50% for Appl.…”
Section: Characterization Of Pimsmentioning
confidence: 99%
“…pH of PIMs that used other alkaline poring agents, such as biochar [28]. Fertilizer glass (FG), on the other hand, does not appear to affect the pH of PIMs, even though it has an alkaline pH [6]. The results obtained showed that the use of pumice scraps in the matrix instead of clay had a positive effect on the porosity of the granules, with values around 50% for APV50, increasing the value as compared to the porosity of PIMs consisting only of clay (43%) reported by Andreola et al [13].…”
Section: Characterization Of Pimsmentioning
confidence: 99%
See 1 more Smart Citation
“…For this research, the aggregates were obtained in the form of a core-shell specimen by formulating an NPK supply system of spent coffee ground, bone ash, and defatted biomass from black soldier fly prepupae. These lightweight materials were designed and customized to provide nutrients over a period of time [18][19][20] Horticultural activities can be carried out indoors, for example, in kitchen gardens, with many advantages. First, there is no seasonality or extreme weather conditions to hinder crop growth, and it allows for the efficient use of resources, such as water and fertilizers, that can be applied according to the crop's specific needs.…”
Section: Introductionmentioning
confidence: 99%
“…MK spectrum shows the Si-O-T (T = Si or Al) bands at 1080 cm −1 . This peak is also recognized as DOSPM (Density of State Peak Maximum) and could be used to follow the geopolymerization [ 18 , 21 , 27 ]. Indeed, this band shifts to a lower wavenumber (1019–1014 cm −1 ) suggesting the increase of Si-O-Al bonds.…”
Section: Resultsmentioning
confidence: 99%